2020
DOI: 10.1002/mds.28016
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Short‐Chain Fatty Acids in Patients With Parkinson's Disease

Abstract: BackgroundShort‐chain fatty acids are exclusively produced by gut microbiota and are reduced in feces of patients with Parkinson's disease (PD). The objective of this study was to conduct a case–control study on peripheral concentration of short‐chain fatty acids based on evidence of pathologic changes in the blood–brain barrier in PD and the possible role of short‐chain fatty acids in blood–brain barrier permeability.MethodsThe plasma short‐chain fatty acid concentration was measured in 38 PD and 33 normal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 40 publications
5
46
1
2
Order By: Relevance
“…Therefore, the immune system of the PD patients is an important target for further therapeutic research [48]. In a recent analysis of the plasma concentration of propionic acid in PD patients, low propionic acid levels correlated with worse motor function as measured with the Unified Parkinson's Disease Rating Score part III (UPDRS-III) [52]. Besides studies describing protective and anti-inflammatory influence, other data also demonstrate negative effects of SCFA.…”
Section: Effectsmentioning
confidence: 99%
“…Therefore, the immune system of the PD patients is an important target for further therapeutic research [48]. In a recent analysis of the plasma concentration of propionic acid in PD patients, low propionic acid levels correlated with worse motor function as measured with the Unified Parkinson's Disease Rating Score part III (UPDRS-III) [52]. Besides studies describing protective and anti-inflammatory influence, other data also demonstrate negative effects of SCFA.…”
Section: Effectsmentioning
confidence: 99%
“…Demographic factors, co-morbidity, and other lipid levels were previously described 16 , which were not different between PD patients and controls, while WCS and K-NMSS score were signi cantly higher in PD patients than those in controls (Table 1).…”
Section: Resultsmentioning
confidence: 52%
“…patients not receiving antibiotics, immune-related drugs, and vaccines (for 3 months, respectively), lipid-lowering drugs (for 1 month), and vitamin supplements, ω-3 fatty acids, prebiotics, and probiotics (for 2 weeks, respectively) 16 . The exclusion criterion was as follows: patients with secondary parkinsonism, other signi cant central nervous system diseases, malignancy within the last 3 years, and signi cant gastrointestinal disorders 16 .…”
Section: Subjectsmentioning
confidence: 99%
“…In support of that, SCFA concentration in feces of PD patients is decreased compared to control individuals [139]. However, Shin et al also observed an increase of plasma SCFA correlated to the PD severity [140]. This result suggests a putative SCFA leakage from intestinal lumen to the bloodstream.…”
Section: Others: Dementia Depression Mental Health…mentioning
confidence: 80%